Análisis de las notas informativas en temas de conservación del medio ambiente, en los medios impresos: diario La Hora, La Crónica y Centinela; y su incidencia en la comunidad lojana. Periodo febrero-septiembre 2014. Lineamientos alternativos - Chamba Rodriguez, Katty Elizabeth (2015)
It is unavoidable to highlight the importance and responsibility that the mass media have in the company, being one of his intentions the service to the community, in the different problematic ones that they afflict to the citizenship. For it, the work consists in to. “ANALYSIS OF THE INFORMATIVE NOTES IN TOPICS OF CONSERVATION OF THE ENVIRONMENT, IN THE PRINTED MEANS: DIARY THE HOUR, THE CHRONICLE AND SENTRY; AND, HIS INCIDENT IN THE COMMUNITY LOJANA. PERIOD FEBRUARY - SEPTEMBER, 2014. ALTERNATIVE LIMITS.”. In the investigation methods were included as; deductive, inductive, analytical, descriptive, statistician, analysis of results, conclusions, recommendations and limits alternative. The sample with which one worked was a total of 400 persons, belonging to Loja's city. The principal aim was to analyze the importance that is giving them to the informative notes in topics of conservation of the environment; in the printed means: Diary The Hour, The chronicle and Sentry and his incident in the citizenship lojana. After the investigative process demonstrated the need of diffusion and information that motivates the printed means and the persons to valuing the environmental problematic and in turn take importance in the publication and interest to read environmental topics. Key words: Conservation, conscience, diffusion and information, importance and interest, ecological journalism.